“Actividades lúdicas para el desarrollo de la autonomía en los niños de preparatoria” - Noroña Guanochanga, Dayanna Lisbeth (2023)
The purpose of this research project is through a substantiated bibliographical review, to analyze the autonomy development in high school children, at Juan Abel Echeverría Educational Unit. The goal research is to diagnose the use of recreational activities for autonomy development. This action is supported by high school teachers, promoting autonomous development in children. Thus, it will facilitate the student’s development through some activities which will help to get a better academic formation such as: the child's personal life making decisions to face different situations of every day with the activities they carry out in their environment. The approach that was used is qualitative, not probabilistic, where the observation technique was proposed to 16 boys and 12 girls, and a question guide to the educational institution teachers. It showed that there is a minimum percentage of students who do not develop well their autonomy and they have difficulties to develop adequately in its context. It is concluded that, from 2 to 3 years old, the child develops skills such as: controlling his body, moving from one place to another without depending on the mother's help, grabbing things without asking help and carry out various activities without depending on someone.